30 great myths about the Romantics - Wu, Duncan (John Wiley & Sons Inc., 2015)
"Wu is not a scholar who trades in faddish or modish opinion, and as its title implies, this is by its very nature an exercise in controversy and debate. The book represents a triumph of individual scholarship over what is claimed as often flawed, albeit consensual, critical opinion. Wu's fluid, readable prose is accessible to all, and his extensive and subtle insights are a joy to read. This unique addition to the student bookshelf provides enjoyment and instruction simultaneously."--Jane Moore, Cardiff University